Intermittent fasting: consider the risks of disordered eating for your patient - Jack Blumberg; Samantha L. Hahn; Jesse Bakke (Clinical Diabetes and Endocrinology, 2023)
Abstract This is a commentary on “Intermittent fasting: is there a role in the treatment of diabetes? A review of the literature and guide for primary care physicians” by Albosta et al. While this article adequately summarized the biochemical clinical advantages and limitations, we feel it failed to mention a few drawbacks, primarily the risk for disordered eating and eating disorders. Here we delve into the emerging data on intermittent fasting or time-restricted feeding in patient populations and urge clinicians to consider these risks prior to encouragement of intermittent fasting.